Epigenetic conversion of conventional T cells into regulatory T cells by CD28 signal deprivation - Mikami, Norihisa; Kawakami, Ryoji; Chen, Kelvin Y; Sugimoto, Atsushi; Ohkura, Naganari; Sakaguchi, Shimon (Proceedings of the National Academy of Sciences - PNAS, 2020)
Foxp3-expressing regulatory T cells (Tregs) can be generated in vitro by antigenic stimulation of conventional T cells (Tconvs) in the presence of TGF-β and IL-2. However, unlike Foxp3 naturally occurring Tregs, such in vitro induced Tregs (iTregs) are functionally unstable mainly because of incomplete Treg-type epigenetic changes at Treg signature genes such as Here we show that deprivation of CD28 costimulatory signal at an early stage of iTreg generation is able to establish Treg-specific DNA hypomethylation at Treg signature genes. It was achieved, for example, by TCR/TGF-β/IL-2 stimulation of CD28-deficient Tconvs or CD28-intact Tconvs without anti-CD28 agonistic mAb or with CD80/CD86-blocked or -deficient antigen-presenting cells. The signal abrogation could induce Treg-type hypomethylation in memory/effector as well as naive Tconvs, while hindering Tconv differentiation into effector T cells. Among various cytokines and signal activators/inhibitors, TNF-α and PKC agonists inhibited the hypomethylation. Furthermore, CD28 signal deprivation significantly reduced c-Rel expression in iTregs; and the specific genomic perturbation of a NF-κB binding motif at the Foxp3 CNS2 locus enhanced the locus-specific DNA hypomethylation even in CD28 signaling-intact iTregs. In addition, in vitro maintenance of such epigenome-installed iTregs with IL-2 alone, without additional TGF-β or antigenic stimulation, enabled their expansion and stabilization of Treg-specific DNA hypomethylation. These iTregs indeed stably expressed Foxp3 after in vivo transfer and effectively suppressed antigen-specific immune responses. Taken together, inhibition of the CD28-PKC-NF-κB signaling pathway in iTreg generation enables de novo acquisition of Treg-specific DNA hypomethylation at Treg signature genes and abundant production of functionally stable antigen-specific iTregs for therapeutic purposes.